The grapes of math : mind stretching math riddles - Tang, Greg.; Briggs, Harry (New York : Scholastic Press, 2001)
Illustrated riddles introduce strategies for solving a variety of math problems by using visual clues.
Publisher's Weekly.
School Library Journal.
Wilson's Children.
4.9.
4.9
3-6
Keywords: Mathematical recreations -- Juvenile literature; Mathematical recreations; Word problems (Mathematics); Mathematical recreations